Recreational Services Valuation of Asiatic Elephants in Developing Countries: A Case Study of Rajaji National Park, India - Gupta, Ajay Kumar; Yadav, Vinod Kumar; Bhushan, Amrendra (Indian Forester, 2015)
National parks are considered as the means of recreation services to a wide section of people, while protecting forest ecosystems. Quantifying recreational services of national parks is vital for park development and sustainable management. This paper attempts to quantify recreational services and examine the payment behavior of visitors of Rajaji National Park, Uttarakhand, India. Data were collected during 2011 through a visitor survey, and the travel cost method was applied to estimate annual recreational value. Recreational value of the park for 2010-11 was estimated to be approximately US3.4 million of which the consumer surplus was approximately US2.8 million, indicating the high social value. It is estimated that if tourist-related amenities are improved the recreational value would increase by about 39%. Coefficients of visit demand determinants have their expected signs and interestingly income and age of visitor are not statistically significant. The study indicates the need for smart investment option for maintaining ecosystem services and biodiversity conservation.